2018
DOI: 10.1021/acs.jafc.8b04001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Short-Chain-Length and Medium-Chain-Length Polyhydroxyalkanoate Blends from Activated Sludge by Manipulating Octanoic Acid and Nonanoic Acid as Carbon Sources

Abstract: The effects of octanoic acid/nonanoic acid and acclimation time on the synthesis of short-chain-length and medium-chain-length PHA blends from activated sludge were investigated. An increased concentration (847−1366 mg/L) of PHAs resulted from 4-month acclimation compared with the concentration derived from 2-month acclimation (450−1126 mg/ L). The content of octanoic acid had a positive linear relationship with the content of even-numbered carbon monomers among the PHAs. The blending products were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Accumulation under oxygen limitation resulted in a maximal PHA content of 76 wt%, where the mcl‐PHA monomers were dominant (i.e., an HHx fraction of 0.14 and an HO fraction of 0.65). This is considerably higher than the 34 wt% reported in previous research investigating octanoate‐fed enrichments, although the mcl‐PHA fraction was similar (i.e., HHx fraction of 0.08 and HO fraction of 0.62) (Chen et al, 2018). Li et al (2021) also obtained a lower PHA content (53 wt%) when enriching with octanoate as a cosubstrate, which also resulted in a significantly lower mcl‐PHA fraction (i.e., HHx fraction of 0.08 and HO fraction of 0.26).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Accumulation under oxygen limitation resulted in a maximal PHA content of 76 wt%, where the mcl‐PHA monomers were dominant (i.e., an HHx fraction of 0.14 and an HO fraction of 0.65). This is considerably higher than the 34 wt% reported in previous research investigating octanoate‐fed enrichments, although the mcl‐PHA fraction was similar (i.e., HHx fraction of 0.08 and HO fraction of 0.62) (Chen et al, 2018). Li et al (2021) also obtained a lower PHA content (53 wt%) when enriching with octanoate as a cosubstrate, which also resulted in a significantly lower mcl‐PHA fraction (i.e., HHx fraction of 0.08 and HO fraction of 0.26).…”
Section: Discussionmentioning
confidence: 95%
“…This intermittent substrate feeding strategy generates a competitive advantage for bacteria that store PHA as carbon and electron reservoir inside their cell. A proof‐of‐principle was already established with C8, C9, C12, and C18 fatty acids (Alaux et al, 2022; Chen et al, 2018; Lee et al, 2011; Shen et al, 2015), where it was found that medium‐chain fatty acids form a suitable substrate for the enrichment of mcl‐PHA producers. The mcl‐PHA fractions of the total PHA content ranged from 0.06 to 0.88.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial synthesis of PHA is challenging, however, using bacterial consortia it can be optimized under reactor conditions. Besides monoculture‐based studies as previously discussed, culture‐independent studies using a hypersaline microbial mat (Martínez‐Gutiérrez et al, 2018) or from the polluted site (López‐Cortés et al, 2008), activated sludge samples (Chen et al, 2018) as well as mixed microbial consortia under different reactor conditions (Carvalho et al, 2014; Coats et al, 2016; Huang et al, 2018a; Miao et al, 2016; Wen et al, 2020) have also highlighted the role of Paracoccus spp. in PHA accumulation and reported the effect of substrate preference, especially carbon source on PHA synthesis.…”
Section: Functional and Genomic Basis For Environmentally Relevant Bi...mentioning
confidence: 99%